2000
DOI: 10.1174/021037000760088071
|View full text |Cite
|
Sign up to set email alerts
|

Dificultades sintácticas y lectura

Abstract: incluso en los buenos lectores. Frecuentemente se piensa en la sintaxis como un ordenamiento formal de las palabras, sin embargo aquí la entenderemos también como una forma de condensar o "empaquetar" la información. Por tanto, una dificultad sintáctica representará también un obstáculo para entender la información. Una parte importante de artículos de prensa y de manuales escolares están escritos con expresiones que presentan dificultades sintácticas. Si ciertas formas de sintaxis utilizadas en algunos textos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…More contact problems in auxetic materials and structures have been considered in some papers (see Refs. [47][48][49][50][51][52] ). Gatt et al [52] concluded that one of the most problematic effects of stent use is contact with a foreign body.…”
Section: Introductionmentioning
confidence: 99%
“…More contact problems in auxetic materials and structures have been considered in some papers (see Refs. [47][48][49][50][51][52] ). Gatt et al [52] concluded that one of the most problematic effects of stent use is contact with a foreign body.…”
Section: Introductionmentioning
confidence: 99%
“…and references therein. Methods for obtaining effective properties for materials that contain energetic surfaces have been developed recently using analytical homogenization [48][49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…Based on Benveniste's formula of Mori-Tanaka method [34], and after a simple deduction, the incremental constitutive relation of composite is given as…”
Section: The Incremental Mori-tanaka Formulamentioning
confidence: 99%